Capital market dynamics in Nigeria : structure, transaction cost and efficiency 1980 - 2006 - Central Bank of Nigeria, Research and Statistics Department (Abuja, Nigeria : Central Bank of Nigeria, 2007)
The study reviews the growth of the capital market in Nigeria and analyzes factors that drive or retard it. It also assesses the efficiency of the Nigerian capital market with the view to enhancing its performance.
Includes bibliographical references.
oif 05/02/2020
Loans
Keywords: Capital markets; Financial markets; Finance; Nigeria